2006
DOI: 10.1111/j.1399-0039.2006.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group and related antigens, natural antibodies and transplantation

Abstract: The current success rate of transplant surgery and immunosuppression has led to a demand for organs that has outstripped the supply. This has required investigation of alternate strategies. Therefore, allotransplantation across the ABO blood group barrier has commenced, and pig-to-human xenotransplantation is under consideration. The first immunological barrier to both these types of transplantation is the prevention of the antibody-mediated rejection. This rejection is a result of natural preformed antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 52 publications
1
68
0
3
Order By: Relevance
“…23-25 This oligosaccharide is one of the major barriers to the transplantation of organs from other mammals in humans and has prompted the development of a strain of pigs in which the gene for α-1,3-galactosyltransferase has been knocked out. 24,26 Natural exposure to galactose-α-1,3-galactose appears to induce the production of IgE antibodies against galactose-α-1,3-galactose in some people. The presence of such IgE antibodies before treatment may put patients who receive monoclonal antibodies containing galactose-α-1,3-galactose at risk for hypersensitivity reactions.…”
Section: Discussionmentioning
confidence: 99%
“…23-25 This oligosaccharide is one of the major barriers to the transplantation of organs from other mammals in humans and has prompted the development of a strain of pigs in which the gene for α-1,3-galactosyltransferase has been knocked out. 24,26 Natural exposure to galactose-α-1,3-galactose appears to induce the production of IgE antibodies against galactose-α-1,3-galactose in some people. The presence of such IgE antibodies before treatment may put patients who receive monoclonal antibodies containing galactose-α-1,3-galactose at risk for hypersensitivity reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocyte membrane presents five major membrane glycoproteins, three of which are heavily sialylated (glycophorins A, B, and C) and two that are not sialylated, but are the major carriers of the ABH(O) blood group antigens (band 3 and band 4.5) (Anstee, 1990). A, B, and H antigens are terminal neutral glycan sequences, which determine the ABO blood type polymorphism (Greenwell, 1997;Milland and Sandrin, 2006;Saitou and Yamamoto, 1997;Yamamoto, 2004). Despite the fact that no major variations in Sia content between erythrocytes of ABO blood groups were reported (Bulai et al, 2003;Cohen et al, 2009), we found that certain Sia binding proteins with the same binding specificity in vitro differentially bind to erythrocytes from the three blood groups (Cohen et al, 2009).…”
Section: Sialylated Clusters On Cells Mediate Differential Bindingmentioning
confidence: 99%
“…[25] Blood group antigens are expressed on all major glycoconjugates of hematopoietic lines and epithelial cells. [1,49] Several galectins are expressed in epithelial cells and colocalize with blood group antigens. [50] Furthermore, galectins bind to glycoproteins that carry ABH antigens.…”
Section: Galectin Ligands Comparisonmentioning
confidence: 99%